The growing needs of genetic counselling—Feasibility in utilization of tele-genetic counselling in Asia and Hong Kong - Chu, Annie Tsz Wai; Chung, Claudia Ching Yan; Hue, Shirley Pik Ying; Chung, Brian Hon Yin (Frontiers in Genetics, 2023)
The need for the expansion of genomic services has been at a record time high in the past decade. As technological advancement continues to strengthen the entire genetic and genomics pipelines and clinical operational workflow, the major challenge remains to be the speed of workforce the development of workforce to meet the service growth. In particular, the international expansion of genetic counselling (GC) services has been a topic of interest for the past few years. GC is an emerging profession in most of Asia, and in many countries the profession of GC often refers to physicians or front-line health workers with expertise in genetics who to provide GC services rather than being a specific independent profession. As genetic and genomic services, especially proper pre-test and posttest GC, expand globally, the pressure need to tackle the longstanding obstacles of shortage of GC personnel shortage and funding issues must not be overlooked. There is an urgent need internationally, and especially in Asia, where GC profession is comparatively less well-established, to seek alternative approaches to meet service demand. The present review serves as the foundation of eexamininges the global development and feasibility of tele-genetics and tele-genetic counselling (TGC), and serves as the foundation to the exploratione of a possible roadmap in Hong Kong via the Hong Kong Genome Project.